Tun Dr. Mahathir Mohamad the 4th Prime Minister of Malaysia, 1981-2003
This programme contain of 100,000 articles, speeches and photos of father of modern Malaysian, Tun Dr. Mahathir Mohamad as a politician, statesman, visionary and world leader.